Increasing the corrosion resistance of heat-resistant alloys for parts of power equipment - Vahrusheva, V.S.; Hlushkova, D.B.; Volchuk, V.M.; Nosova, T.V.; Mamhur, S.I.; Tsokur, N.I.; Bagrov, V.A.; Demchenko, S.V.; Ryzhkov, Yu.V.; Scrypnikov, V.O. (Вопросы атомной науки и техники, 2022)
For the manufacture of parts and assemblies of the turbopump unit of details of power equipment, welded joints with corrosion resistant steels and heat-resistant alloys are used, requiring various modes heat treatment to achieve the required level of mechanical properties. In the manufacture of parts and assemblies of details of power equipment at the machine-building enterprises of Ukraine, it became necessary to replace semi-finished products. It is necessary to replace sheet products from high-alloy alloys ХН67МВТЮ and 06Х15Н6МВФБ with one alloy with a high complex of physical and mechanical characteristics. In the work, as a replacement for the applied heat-resistant alloys, Inconel 718 alloy welded to 316L steel. Samples of welded joints, processed according to the recommended mode, showed increased corrosion resistance. Для виготовлення деталей енергетичного обладнання застосовуються зварні з’єднання з корозійно-стійкими сталями та жароміцними сплавами, що потребують різних режимів термічної обробки для досягнення необхідного рівня механічних властивостей. При виготовленні деталей енергетичного обладнання на машинобудівних підприємствах України виникла потреба заміни напівфабрикатів. Необхідна заміна листового прокату з високолегованих сплавів ХН67МВТЮ та 06Х15Н6МВФБ на один сплав із високим комплексом фізико-механічних характеристик. У роботі в якості заміни жароміцних сплавів обраний сплав Inconel 718 у зварному з’єднанні зі сталлю 316L. Зразки зварних з’єднань, які оброблені за рекомендованим режимом, показали підвищену корозійну стійкість.